Vietnamese Civil Servants’ Public Service Ethics (Journal of Namibian Studies : History Politics Culture, 2022)
In public service activities, the ethics of civil servants is considered one of the criteria for evaluating the quality of civil servants, often clearly legislated. This is an important assessment content because civil servants are those who exercise state power and serve the people. The issue of public service ethics is identified as having many contents; In this study, the author inherits some basic content from previous studies to build a theoretical framework for research on civil servants' public service ethics, including political thoughts; and public service responsibilities. The author surveyed 300 leaders of commune-level government agencies of 3 provinces representing 3 regions of Vietnam, including Lang Son province (Northern region), Quang Binh province (Central region), and Tay Ninh province (Southern region). The survey aims to collect information to evaluate the ethical practice of civil servants' public service ethics of commune-level - those who directly handle people's requests. Survey results show that commune-level civil servants have public service ethics that meet the requirements of performing public duties expressed through political thoughts; and public service responsibilities. However, leaders of local government agencies evaluate civil servants' public responsibilities at a lower level. From the results of this research, the author discusses practical issues that need to be researched and adjusted to improve the quality of local civil servants to meet the requirements of serving the people.